Asymptotic Dynamics of a New Mechanochemical Model in Biological Patterns - Liu, Aibo; Liu, Changchun (Mathematical Modelling and Analysis, 2017)
In this paper, we prove the existence of attractor for a new mechanochemical model with Neumann boundary conditions on a bounded domain of space dimension n ≤ 3. Based on the regularity estimates for the semigroups and the classical existence theorem of global attractors, we prove that the mechanochemical model possesses a global attractor and Hk attractor.